The language of images – metaphor and metonymy in film - Fabčič, Melanija Larisa (Slavia Centralis, 2022)
Does the audio-visual medium of film contain metaphors and metonymies? Most film scholars think so. When considering the difference between visual (cinematographic, film) and linguistic metaphors and metonymies however, such opinions are not so uniform. Metaphorical and metonymical processes in film are at the centre of our article. We aim to describe and define the specifics of visual metaphors and metonymies through presenting an overview of the different theories concerning visual metaphors and metonymies (from Eisenstein to Metz and contemporary monographs). We will then observe and interpret the use of visual rhetorical means of expression (film metaphors and metonymies) in select classical and modern movies. We postulate that film is a ‘kind of language’1 (Metz 1974/1991: 40) and therefore has its own special rhetoric (of image and sound) that is comparable to verbal language yet also different.
Keywords: film language; film as language; film metaphor; film metonymy